Application of home-made lipase in the production of geranyl propionate by esterification of geraniol and propionic acid in solvent-free system. Issue 1 (January 2015) - Ferraz, Lenir Inês Rigoli; Possebom, Géssica; Valandro Alvez, Emilly; Luiz Cansian, Rogério; Paroul, Natália; de Oliveira, Débora; Treichel, Helen
Abstract This work relates the maximization of geranyl propionate production by esterification in solvent-free system using a lipase extract from Penicillium crustosum. A sequencial strategy of experimental design was carried out followed by a kinetic study. The study of reuse of the non-commercial immobilized enzymatic extract was also carried out. The operating conditions that maximized geranyl propionate production were determined to be 60 °C, geraniol to propionic acid mole ratio of 5:1, 150 rpm and 50 wt% of lipase extract, resulting in a conversion of about 53%. A kinetic study was performed and the results allow to conclude that an excess of alcohol (alcohol to acid mole ratio of 5:1), relatively low enzyme concentration (50 wt%) and 40 °C afforded good conversions after 50 min. The relative activity decreased along the reuse, retaining around 50% of the same after four cycles. The decrease in the activity of the immobilized extract was accompanied by a drop in geranyl propionate conversions. New experimental data on enzymatic esterification of geraniol and propionic acid for geranyl propionate production are reported in this work, showing a promising perspective of using low cost biocatalysts to overcome the well-known drawbacks of the chemical-catalyzed route.